Pengembangan Desain dan Fabrikasi Mesin Pencacah Es Balok - PS, Rahmat; Mu'tasim; Salam, Abdul; Hasanah Mihdar, Uswatul (Jurnal Teknik Mesin Sinergi, 2026)
Based on observations conducted at several fish auction sites and fish vendors around fish markets, it was found that these locations require approximately 40 blocks of ice per day for fish preservation. Several limitations of the existing block ice crushing machines include the high workload required to insert ice blocks into the machine inlet and the production of only one type of crushed ice, namely a mixture of fine and coarse fragments. This applied design research aims to develop a block ice crushing machine capable of producing two types of crushed ice, namely fine and coarse fragments with more uniform particle sizes, and to evaluate the machine performance based on rotational speed variations in terms of crushed ice quality and production capacity. The research methodology consisted of several stages, including designing the machine structure with a foldable inlet channel, detachable crushing rods on the crushing drum, and a more practical construction design. The subsequent stages involved machine fabrication, machine performance testing at various rotational speeds, and the calculation of manufacturing costs. The results show that the best performance for fine ice crushing was achieved at a machine speed of 1100 rpm with particle sizes ranging from 0.5–2 cm, while coarse crushing was optimal at 900 rpm with particle sizes ranging from 5–8 cm. The manufacturing cost for producing this block ice crushing machine was Rp 5,253,438.